Biological Flora of the British Isles: Milium effusum. (1st March 2017) - De Frenne, Pieter; Brunet, Jörg; Cougnon, Mathias; Decocq, Guillaume; Graae, Bente J.; Hagenblad, Jenny; Hermy, Martin; Kolb, Annette; Lemke, Isgard H.; Ma, Shiyu; Orczewska, Anna; Plue, Jan; et al.
Summary: This account presents information on all aspects of the biology of Milium effusum L. (Wood Millet) that are relevant to understanding its ecological characteristics and behaviour. The main topics are presented within the standard framework of the Biological Flora of the British Isles : distribution, habitat, communities, responses to biotic factors, responses to environment, structure and physiology, phenology, floral and seed characters, herbivores and disease, history, and conservation. The grass Milium effusum is a common species of mature woodland in central and southern England, but is less common in the wetter parts of northern England, Wales, Scotland and Ireland. World‐wide, the species is native to many temperate, boreal, subarctic and subalpine parts of the northern hemisphere: from eastern North America across most of Europe (excluding Mediterranean climates) to the Ural Mountains and Black Sea, extending eastwards to the Himalaya, Korea and Japan. Wood Millet is a shade‐tolerant, relatively tall grass (up to 1·8 m) producing up to 700 caryopses per individual. It is characteristic of temperate deciduous woodland, but can also occur in other woodland and forest types and even in scrub, alpine meadows, along railways and roads, and on rocks. In woods, it is one of the most conspicuous plants of the herb layer in the early summer after the disappearance of spring flowering species. While the species is generally considered an ancient woodland indicator in England and western Europe, it is also known to colonize secondary, post‐agricultural forests relatively rapidly in other areas such as Denmark, southern Sweden and Poland. The species has a wide amplitude in terms of soil acidity and nutrient availability, but predominantly grows on soils of intermediate soil fertility and soil pH and with high organic matter concentration. However, M. effusum can tolerate large quantities of tree‐leaf litter on the forest floor and is able to grow on very acidic soils. Changes in land use, climate, densities of large herbivores and atmospheric deposition of nitrogen are having effects on populations of Wood Millet. Significant responses of the life‐history traits and population characteristics have been detected in response to environmental variation and to experimental treatments of temperature, nutrients, light and acidity. In many of its habitats across its range, M. effusum is currently becoming more frequent. During the last century, its mean elevation of occurrence in upland areas of Europe has also increased by several hundreds of metres. Typically, management actions are directed towards the conservation of its main habitat type (e.g. ancient woodlands of the Milio‐Fagetum association) rather than to the species specifically. Abstract : The shade‐tolerant grass Milium effusum is a common feature of mature woodlands in England, but is less common in the wetter parts of the British Isles. It has a wide distribution in the northern hemisphere from eastern North America to Japan. Miliumeffusum is currently becoming more frequent in many of its habitats across its range, probably because of a combination of changes in land use, climate, increased densities of large herbivores and atmospheric N deposition.